Estimating a Poverty Line for Brazil Based on the 2017/18 Household Budget Survey - Lara Ibarra, Gabriel; Paffhausen, Anna Luisa; Duque, Daniel (World Bank, Washington, DC, 2021)
This study applies the cost-of-basic-needs approach to estimate food and total poverty lines for the Brazilian case. Using detailed data on expenditures from a 2017/18 household budget survey and caloric information from the Brazilian Table of Food Composition, calorie intake is assigned to more than 1,400 items to estimate the cost per calorie for a representative group of the population. The preferred results estimate the value of the food poverty line at R$258 (in 2018 urban Southeast prices), and the lower total poverty line (covering also nonfood necessities) at R$455. Robustness checks show that varying the assumptions leads to qualitatively similar results. The findings are also close in value to lines found in earlier studies and the societal poverty line. Finally, this work provides a data-driven validation of the income threshold used to determine eligibility for Brazil’s social registry.